"Spontaneous bubble-template" assisted metal–polymeric framework derived N/Co dual-doped hierarchically porous carbon/Fe3O4 nanohybrids: superior electrocatalyst for ORR in biofuel cells. Issue 23 (31st May 2016) - Cao, Chun; Wei, Liling; Su, Min; Wang, Gang; Shen, Jianquan
Abstract : A "spontaneous bubble-template" assisted metal–polymeric framework derived porous N/Co–C and Fe3 O4 nanohybrid was employed as an efficient ORR electrocatalyst in MFCs. Abstract : A "Spontaneous bubble-template" method is fascinating in that bubbles are formed in situ during material processing and employed as a template for fabricating unique structures, which has not been reported in material science. It is sustainable, green and efficient in that no extra additives or post-treatment are used. Herein, novel metal–polymeric framework derived hierarchically porous carbon/Fe3 O4 nanohybrids are prepared using a "spontaneous bubble-template" method by one-step carbonization. During the carbonization process, N and Co are self-doped on porous carbon in which in situ grown nano Fe3 O4 is embedded (Fe3 O4 @N/Co–C). The as-prepared Fe3 O4 @N/Co–C displays a three-dimensional interpenetrating morphology (electrochemical active area: 729.89 m 2 g −1 ) with well-distributed Fe3 O4 nanoparticles (20–50 nm) which are coated with a carbon layer (3–5 nm). Fe3 O4 @N/Co–C exhibits remarkable oxygen reduction activity in biofuel cells with a distinct output voltage (576 mV) and power density (918 mW m −2 ), which are 3.6% and 17.8% higher than those of Pt (0.5 mg cm −2 ), respectively. Besides biofuel cells, Fe3 O4 @N/Co–C may also have the potential for application in chemical fuel cells, since it demonstrates better oxygen reduction activity in electrochemical measurements. Thus, with the virtues of its low-cost, facile synthesis and large-scale preparation, Fe3 O4 @N/Co–C is a promising electrocatalyst for the oxygen reduction reaction and application in biofuel cells.